A quantity to identify turbulence related sound generation on surfaces - Delfs, Jan W.; Ruck, Richard (Journal of sound and vibration, 2024)
This contribution addresses the problem of identifying sources of sound on aerodynamic surfaces subject to turbulent flow. A quantity is proposed, which identifies the location of the sound generation and serves as well to quantify these sources. The suggested concept reduces fluctuating surface pressure data to the part of the pressure which is actually relevant for sound generation (representing only a very small fraction of the former). The focus is put on the interpretation of surface pressures rather than prediction, i.e. data is assumed known, typically obtained from scale-resolving numerical simulations of the turbulent flow around the surfaces. The idea is to generate knowledge from this data, as a basis for designing more silent aero shapes. The localization of sources of sound generated aerodynamically is usually accomplished by phased microphone array (numerical) beamforming techniques in various variants involving acoustic propagation of source data to the acoustic farfield and subsequent data processing. This “detour” to the acoustic farfield indeed enables the separation of sound and aerodynamic (nearfield) data. The proposed approach explicitly uses nearfield information of the surface pressure field to identify and quantify aerodynamic sources of sound on surfaces without the need to introduce beamforming. The main hypothesis of this approach states that sound is generated where the mirror principle of flow quantities, ideally satisfied at plane hard surfaces, is violated. It turns out that the hypothesis is equivalent to the statement that aerosound is produced by diffraction of the pressure nearfield incident to a surface and as such intimately related to curvature. A physical quantity is proposed to quantify and thereby localize this source of sound. The method to determine the quantity is successfully validated for the cases of leading and trailing edge sound generation at an airfoil. [Display omitted] •A first principles based aeroacoustic source localization concept is derived.•An aeroacoustic surface source quantity q is derived which enables the source localization.•The source localization relies on surface pressure and not on beamforming.•The diffractional part of surface scattering generates sound; the reflexional part does not.•q is objective, shows super resolution for localization, forms basis for optimization.